A flaw in applying the FRET technique to evaluate the distance between ligands and tryptophan residues in human serum albumin: Proposal of correction - Povinelli, Ana Paula Ribeiro; de Carvalho Bertozo, Luiza [UNESP]; Zazeri, Gabriel; Ximenes, Valdecir Farias [UNESP] (Elsevier, 2023)
Due to its primordial function as a drug carrier, human serum albumin (HSA) is extensively studied regarding its binding affinity with developing drugs. Förster resonance energy transfer (FRET) is frequently applied as a spectroscopic molecular ruler to measure the distance between the binding site and the ligand. In this work, we have shown that most of the published results that use the FRET technique to estimate the distance from ligands to the binding sites do not corroborate the crystallography data. By comparing the binding affinity of dansyl-proline with HSA and ovotransferrin, we demonstrated that FRET explains the quenching provoked by the interaction of ligands in albumin. So, why does the distance calculation via FRET not corroborate the crystallography data? We have shown that this inconsistency is related to the fact that a one-to-one relationship between donor and acceptor is not present in most experiments. Hence, the quenching efficiency used for calculating energy transfer depends on distance and binding constant, which is inconsistent with the correct application of FRET as a molecular ruler. We have also shown that the indiscriminate attribution of 2/3 to the relative orientation of transition dipoles of the acceptor and donor (κ2) generates inconsistencies. We proposed corrections based on the experimental equilibrium constant and theoretical orientation of transition dipoles to correct the FRET results.
Keywords: Albumin; Dansyl-proline; Förster resonance energy transfer; Orientation factor; Ovotransferrin